Productivity Changes of Pharmaceutical Industry in Bangladesh: Does Process Patent Matter? - Azad, Md Abul Kalam; Munisamy, Susila; Kwek, Kian Teng; Abdul Mutalib, Muzalwana; Saona, Paolo (SAGE Publications, 2018)
The large pharmaceutical companies in Bangladesh have currently expertise in process patent activities rather than in product patent. Such industry condition can easily generate a high profile in production and sales. However, achieving sustainability in the long run using automation and purchase of the patent only seems unsuitable. In the last two decades, it is found that both the medium and big size companies have leaned on introducing automation in their existing product plants, improving them in nothing but production. The article measures technical efficiency using data envelopment analysis (DEA) over the period of 2009–2013. We use one output—annual sales—and three inputs, namely, (a) fixed asset, (b) raw material cost and (c) cost of salary to run Malmquist total factor productivity (TFP) index. The major contributor of TFP growth is found due to the technological positive growth with a value of 10.8 per cent annually. Moreover, all changes of technical efficiency, pure efficiency and scale efficiency have regressed with values of 5.5 per cent, 2.1 per cent and 3.5 per cent, respectively. Thus, the gains in productivity are entirely due to technological advancements and not for technical improvements. The main source of inefficiency in pharmaceutical industry is scale inefficiency rather than pure technical inefficiency. Limitations and policy implications are addressed.